The relative age effect in combat sports: an analysis of Olympic judo athletes 1964-2012 - Albuquerque, M. R.; Franchini, E.; Lage, G. M.; da Costa, V. T.; Costa, I. T.; Malloy-Diniz, L. F. (Perceptual and Motor Skills, 2015)
This study assessed the relative age effect (RAE) in judo athletes who participated in the Olympic Games from 1964 to 2012. The names and birthdates of the Olympic judo athletes were collected from open-access websites. Data from male (n = 1,762) and female (n = 665) competitors were analyzed separately. Chi-squared tests were performed to investigate REA in medalists, and by weight categories and sexes. When the analyses used semesters to divide the period when the athletes were born, a RAE was found in male heavyweight athletes and male medallists. Thus, in a selected group of judo athletes who had participated at the highest competitive level, RAEs were present in both athletes who won Olympic medals and heavyweight athletes in the male group.